The genome of cultivated sweet potato contains Agrobacterium T-DNAs with expressed genes: An example of a naturally transgenic food crop - Kyndt, Tina; Quispe, D.; Zhai, H.; Jarret, Robert L.; Ghislain, M.; Liu, Q.; Gheysen, G.; Kreuze, Jan F. (National Academy of Sciences, 2015)
We communicate the rather remarkable observation that among 291 tested accessions of cultivated sweet potato, all contain one or more transfer DNA (T-DNA) sequences. These sequences, which are shown to be expressed in a cultivated sweet potato clone (“Huachano”) that was analyzed in detail, suggest that an Agrobacterium infection occurred in evolutionary times. One of the T-DNAs is apparently present in all cultivated sweet potato clones, but not in the crop’s closely related wild relatives, suggesting the T-DNA provided a trait or traits that were selected for during domestication. This finding draws attention to the importance of plant–microbe interactions, and given that this crop has been eaten for millennia, it may change the paradigm governing the “unnatural” status of transgenic crops.